Esporotricosis del pabellón auricular. Comunicación de un caso atípico simulando una celulitis bacteriana - Ochoa Reyes, Juan; Ramos Martínez, Ernesto; Treviño Rangel, Rogelio de Jesús; González González, Gloria María; Bonifaz, Alexandro (2017)
Auricular sporotrichosis. Atypical case report simulating bacterial cellulitis Sporotrichosis is the most common subcutaneous or implantation mycosis in Mexico. The case of a preauricular cutaneous-fixed sporotrichosis simulating atypical bacterial cellulitis is reported in an elderly patient with no history of trauma. The biopsy showed a suppurative granuloma with scarce yeast. Sporothrix schenckii was identified in the culture and confirmed by molecular biology. She was treated with itraconazole and a clinical and mycological cure was obtained. The case of atypical presentation is presented, coming from a semi-arid zone with extreme weather. Key words: Sporotrichosis; Sporothrix schenckii; fixed-cutaneous; bacterial cellulitis; itraconazole; PCR Palabras clave: Esporotricosis; Sporothrix schenckii; cutánea-fija, celulitis bacteriana; itraconazol, RPC.